Dynamic microtubules promote synaptic NMDA receptor-dependent spine enlargement. - Elliott B Merriam; Derek C Lumbard; Chris Viesselmann; Jason Ballweg; Matthew Stevenson; Lauren Pietila; Xindao Hu; Erik W Dent (PLoS ONE, 2011)
Most excitatory synaptic terminals in the brain impinge on dendritic spines. We and others have recently shown that dynamic microtubules (MTs) enter spines from the dendritic shaft. However, a direct role for MTs in long-lasting spine plasticity has yet to be demonstrated and it remains unclear whether MT-spine invasions are directly influenced by synaptic activity. Lasting changes in spine morphology and synaptic strength can be triggered by activation of synaptic NMDA receptors (NMDARs) and are associated with learning and memory processes. To determine whether MTs are involved in NMDAR-dependent spine plasticity, we imaged MT dynamics and spine morphology in live mouse hippocampal pyramidal neurons before and after acute activation of synaptic NMDARs. Synaptic NMDAR activation promoted MT-spine invasions and lasting increases in spine size, with invaded spines exhibiting significantly faster and more growth than non-invaded spines. Even individual MT invasions triggered rapid increases in spine size that persisted longer following NMDAR activation. Inhibition of either NMDARs or dynamic MTs blocked NMDAR-dependent spine growth. Together these results demonstrate for the first time that MT-spine invasions are positively regulated by signaling through synaptic NMDARs, and contribute to long-lasting structural changes in targeted spines.